A three-dimensional bioenergetic population model of anchovy and sprat in the Black Sea. Hindcast (1960-2020) and sensitivity simulations - Athanasios Gkanasos; Kostas Tsiaras; George Triantafyllou (Frontiers in Marine Science, 2025)
This study presents the development of a three-dimensional, Wisconsin-type bioenergetic/population model, two-way coupled with a biogeochemical model (POM-ERSEM) that simulates physical, chemical, and biological processes in the marine environment, to investigate the dynamics of anchovy ( Engraulis encrasicolus ) and sprat ( Sprattus sprattus )—the two most ecologically and economically significant fish species in the Black Sea. The model simulates key energetic processes, including growth and reproduction, and, in conjunction with the population module, it was used to estimate the two species biomass spatiotemporal variability. A long-term simulation over 1960–2020 period was performed, using ECMWF ERA5 atmospheric forcing. The model successfully reproduces the interannual variability in both species’ stocks and highlights the formation of distinct anchovy and sprat habitats. To explore the effects of atmospheric forcing, a perpetual simulation for the same period was conducted. The analysis reveals a negative correlation between sea surface temperature and anchovy biomass, primarily due to reduced adult weight and increased energetic demands, which negatively impact productivity. In contrast, sprat populations exhibit a positive response to warming, with increased survival rates across life stages despite a decline in egg productivity due to habitat limitations. Furthermore, the study examines the species responses to varying fishing pressure. While both species and especially sprat, are threatened by overfishing, they demonstrate rapid recovery rates, indicating susceptibility to effective management measures. These findings provide valuable insights into the sustainable exploitation of anchovy and sprat under changing climatic conditions, aiding in the development of adaptive fisheries management strategies.

Stopping Macroplastic and Microplastic Pollution at Source by Installing Novel Technologies in River Estuaries and Waste Water Treatment Plants: The CLAIM Project - Athanasios Gkanasos; Kostas Tsiaras; George Triantaphyllidis; Aleksandros Panagopoulos; George Pantazakos; Tristan Owens; Christos Karametsis; Annika Pollani; Elisabeth Nikoli; Nikolaos Katsafados; George Triantafyllou (Frontiers in Marine Science, 2021)
Marine pollution from debris is a major issue nowadays, since every year large amounts of litter enter into the sea. Under the Horizon 2020 framework and within the Cleaning Litter by developing and Applying Innovative Methods in European Seas (CLAIM) project, innovative devices were designed, developed, tested and applied in laboratory and in the field. These consisted of a system named CLEAN TRASH for the prevention of macrolitter in river estuaries before entering the Sea and a filtering system for microplastics (MPs), to be placed at waste water treatment plants (WWTP). Laboratory experiments showed that macrolitters were blocked by 90% by the CLEAN TRASH system, while during the sea testing period at the Kifissos river estuary, a significant source of terrestrial based litter for the Saronikos Gulf, a total amount of 1,175 kg of litter was collected in 38 days before entering the sea, of which the 708 kg (60%) were plastic debris of various sizes and another 164 kg (14%) of styrofoam parts. The lab scale prototype of the filtering system for MPs had an efficiency of about 95%. The upscaled device was tested at the Megara WWTP and was able to withhold a significant amount of MPs. The theoretical contribution of such devices toward the reduction of plastic pollution in the Saronikos Gulf area and the Natura conservation areas therein, was also studied with the use of a 3-D coupled Hydrodynamic-Lagrangian litter tracking model. In all experiments performed, the installation of the above devices for a period of 2 years, resulted in a microplastics reduction by about 87% and a macroplastics reduction ranging from 13 to 43%, depending on the sources.

A three dimensional, full life cycle, anchovy and sardine model for the North Aegean Sea (Eastern Mediterranean): Validation, sensitivity and climatic scenario simulations - ATHANASIOS GKANASOS; EUDOXIA SCHISMENOU; KOSTAS TSIARAS; STYLIANOS SOMARAKIS; MARIANNA GIANNOULAKI; SARANTIS SOFIANOS; GEORGE TRIANTAFYLLOU (Mediterranean Marine Science, 2021)
We present the development of a 3D full-lifecycle, individual-based model (IBM) for anchovy and sardine, online coupled to an existing hydrodynamic/biogeochemical low-trophic level (LTL) model for the North Aegean Sea. It was built upon an existing 1D model for the same species and area, with the addition of a horizontal movement scheme. In the model, both species evolve from the embryonic stage (egg+yolk sac larva) to the larval, juvenile, and adult stages. Somatic growth is simulated with the use of a “Wisconsin” type bioenergetics model and fish populations with an adaptation of the ‘super individuals’ (SI) approach. For the reference simulation and model calibration, in terms of fish growth and population biomass, the 2000-2010 period was selected. Interannual biomass variability of anchovy was successfully represented by the model, while the simulated biomass of sardine exhibited low variability and did not satisfactorily reproduce the observed interannual variability from acoustic surveys. The spatial distribution of both species’ biomass was in relatively good agreement with field data. Additional single-species simulations revealed that species compete for food resources. Temperature sensitivity experiments showed that both species reacted negatively to a temperature increase. Anchovy, in particular, was more affected since its spawning and larval growth periods largely overlap with the period of maximum yearly temperature and low prey concentration. Finally, simulation experiments using IPCC climatic scenarios showed that the predicted temperature increase and zooplankton concentration decrease in the future will negatively affect anchovy, resulting in sardine prevalence.

Decadal scale variability of sea surface temperature in the Mediterranean Sea in relation to atmospheric variability - Nikolaos Skliris; Sarantis Sofianos; Athanasios Gkanasos; Anneta Mantziafou; Vasilis Vervatis; Panagiotis Axaopoulos; Alex Lascaratos (Ocean Dynamics, 2012)